PENGARUH PENEMPATAN KERJA DAN MOTIVASI TERHADAP KINERJA CADDY PT GADING RAYA GOLF, SERPONG – TANGERANG - Mochamad Soelton; Catur Widayati (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
Problems faced by management of Golf and Country club are the low-performance Caddy and allegedlyinfluenced by various factors, among others, Employment and Motivation.To analyze the problem, then use the method of multiple linear regression analysis. The study wasconducted on 100 respondents with saturated samples (census methods). The purpose of this study was toanalyze the influence of Employment, Motivation to Performance Caddy. From the test results obtainedregression independent variables Employment and fairly strong positive correlation (R) 0.559 with significant values 0.00 (<0.01), for the independent variable motivation and positive correlation (R) 0.637with a strong significant 0.00 ( <0.01). R-square value indicates the value of 0.469, it could mean that46.9% Performance of Caddy PT. Gading Raya Golf can be explained by the variable Employment andmotivation, the remaining 53.1% is explained by other variables. Performance Caddy conclusion is affectedby the Employment and Motivation. It is therefore advisable to strengthen continuous training, especiallyrelating to the rule of golf, product knowledge of golf.